The Role of The Agreement on Trade Related Aspects of Intellectual Property Rights (trips) in The System Intellectual Property Protection (Vallis Aurea, 2015)
The Agreement on Trade Related Aspects of Intellectual Property Rights is one of the recent treaties in the system of intellectual property protection. This agreement represents an annex to the Agreement Establishing the World Trade Organization and is not in the system of the World Intellectual Property Organization. According to the TRIPS Agreement, protection of intellectual property should contribute to the promotion of technological innovation, transfer and dissemination of technologies for the mutual benefit of producers and users of technological knowledge in ways that incite social and economic development, as well as balancing the rights and obligations. TRIPS contains some of the principles and clauses that are specific to international trade agreements, such as most-favored-nation clauseand it gave the definition of each of the industrial property rights. These definitions will contribute to the harmonization of national legislation in this field.Unlike earlier treaties, TRIPS contains detailed provisions relating to the enforcement of intellectual property rights.Thanks to the mechanism of sanctions under the World Trade Organization, TRIPS became an umbrella agreement in the system of intellectual property protection.